Management of the extensive thoracic defects after deep sternal wound infection with the rectus abdominis myocutaneous flap: A retrospective case series. Issue 16 (April 2017) - Li, Yue-Hua; Zheng, Zhao; Yang, Jiaomei; Su, Lin-Lin; Liu, Yang; Han, Fu; Liu, Jia-Qi; Hu, Da-Hai
Abstract : Abstract: Deep sternal wound infection is a severe complication after open heart surgery. According to the different severity and dimensions of the deep sternal wound infection, the treatment method is different. In this study, we aimed to describe our experience with the rectus abdominis myocutaneous flap for large sternal wound management, especially when 1 or 2 internal mammary arteries were absent. Between October 2010 and January 2016, a retrospective review of 9 patients who suffered from the extensive thoracic defects after deep sternal wound infection was conducted. All of these sternal defects encompassed almost the full length of the sternum after debridement. Defect reconstruction was achieved by covering with a rectus abdominis myocutaneous flap. When the ipsilateral or bilateral internal mammary artery had been harvested previously, we took advantage of the inferior epigastric artery to provide additional blood supply to the rectus abdominis myocutaneous flap. Thus, this flap had a double blood supply. There was no recurrent infection in all 9 patients. Three patients received the rectus abdominis myocutaneous flap with a double blood supply. Flap complications occurred in 2 patients (22%). One patient who did not have the double blood supply flap suffered from necrosis on the distal part of the flap, which was then debrided and reconstructed with a split-skin graft. The other patient had a seroma at the abdomen donor site and was managed conservatively. None of the patients died during the hospital stay. This study suggests that the rectus abdominis myocutaneous flap may be a good choice to repair the entire length of sternal wound. When 1 or 2 internal mammary arteries have been harvested, the inferior epigastric artery can be anastomosed to the second intercostal artery or the internal mammary artery perforator to provide the rectus abdominis myocutaneous flap with a double blood supply.